2021
DOI: 10.1101/gr.275133.120
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements and their KZFP controllers are drivers of transcriptional innovation in the developing human brain

Abstract: Transposable elements (TEs) account for more than 50% of the human genome and many have been co-opted throughout evolution to provide regulatory functions for gene expression networks. Several lines of evidence suggest that these networks are fine-tuned by the largest family of TE controllers, the KRAB-containing zinc finger proteins (KZFPs). One tissue permissive for TE transcriptional activation (termed “transposcription”) is the adult human brain, however comprehensive studies on the extent of this process … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 96 publications
1
34
0
Order By: Relevance
“…3A). These data suggest that the CB exhibits, not only different TE and gene expression compared to other brain regions as previously described (Playfoot et al 2021;Li et al 2018), but also differences in TE-embedded miRNA expression.…”
Section: Te-embedded Mirnas Are Spatially Expressedsupporting
confidence: 81%
“…3A). These data suggest that the CB exhibits, not only different TE and gene expression compared to other brain regions as previously described (Playfoot et al 2021;Li et al 2018), but also differences in TE-embedded miRNA expression.…”
Section: Te-embedded Mirnas Are Spatially Expressedsupporting
confidence: 81%
“…Moreover, SVAs are among the few transposable elements that still exhibit active transposition in the human genome. We and others have previously revealed that SVAs can be source of enhancers in primates (Playfoot et al, 2021; Pontis et al, 2019; Trizzino et al, 2017; Trizzino et al, 2018). The repression of some SVAs by specific zinc-finger proteins at specific stages of neuronal development is also a crucial mechanism for successful neurogenesis (Playfoot et al, 2021; Pontis et al, 2019; Turelli et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…We and others have previously revealed that SVAs can be source of enhancers in primates (Playfoot et al, 2021; Pontis et al, 2019; Trizzino et al, 2017; Trizzino et al, 2018). The repression of some SVAs by specific zinc-finger proteins at specific stages of neuronal development is also a crucial mechanism for successful neurogenesis (Playfoot et al, 2021; Pontis et al, 2019; Turelli et al, 2020). Here, we demonstrate that SVAs are pervasive regulators of hippocampal neurogenesis and they act as enhancers in the hippocampal intermediate progenitor population.…”
Section: Discussionmentioning
confidence: 90%
“…TEs that are still mobile within an individual's genome mobilise predominantly in germ cells and during early embryogenesis [30,31]. Since TEs often include TSSs and other regulatory sequences in their own sequence, their mobilisation has contributed to the formation of novel tissue-specific promoters and transcription factor binding sites (TFBSs), which now have a role in ensuring the correct spatiotemporal gene expression patterns during development [32,33]. Furthermore, TE mobilisation also occurs in somatic cells.…”
Section: Key Pointsmentioning
confidence: 99%